From teacher to mentor: a case study on the development of mentoring skills - Da Silva, Larissa Goulart (Revista Odisseia, 2017)
The purpose of this paper is twofold. First, based on a literature review, the characteristics of a good mentoring practice are presented; and second, based on an action research I analyze how one teacher developed these characteristics (or not) during the process of becoming a mentor. Concerning the first objective, several researchers (MAYNARD, 2000; ORLANDI, 2001; RANDALL; THORNTON, 2001) have addressed the mentoring process. Considering their findings, it is possible to devise a list of good mentoring practices, consisting of characteristics, such as sharing expertise, developing an interpersonal relationship, understanding the mentoring situation, challenging and supporting, among others. Regarding the second objective, the data presented here are transcripts of the interactions between a novice mentor and student-teachers. These interactions show that even though all the characteristics of a good mentor were displayed during these sessions of mentoring, the extent to which they were displayed varies considerably.